PENGARUH MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA EDUCAPLAY TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SDN 060847 MEDAN PETISAH - Tamba, Santa Adolia; Anton Sitepu; Frikson Jony Purba; Rizki Bastanta; Heka Maya Sembiring; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the teams games tournament model assisted by educaplay on the learning outcomes of fourth grade students at SDN 060847 Medan Petisah. Learning Year 2024/2025. In this study using quantitative methods, the population of this study were all grade IV SDN 060847 and the number of samples of this study were 25 students based on purposive sampling technique. Data on the teams games tournament learning model can be obtained from a questionnaire distributed to students and student learning outcomes can be obtained from the Pretest and Posttest scores of students in the 2024/2025 learning year. The results of this study indicate that student learning outcomes using the teams games tournament model are included in the very good category with an average Posttest of 83.20 and an average questionnaire score of 92,58. Furthermore, the results of hypothesis testing show tcount of 6,282 while t table is 2.060. So it is proven that Ho is rejected and Ha is accepted. Through the t-test, it can be concluded that there is a significant positive effect between the team games tournament learning model assisted by educaplay media on student learning outcomes in class IV IPAS subjects SDN 060847 Medan Petisah 2024/2025 Learning Year.